120k views
1 vote
Edwin was evaluating the expression below when a = 3 and b = -6

Edwin was evaluating the expression below when a = 3 and b = -6-example-1
User Natronite
by
4.8k points

2 Answers

9 votes

-- - - - - - - - - - - - - - - -- - - -- - - - - - - - - - - - - - - -- - - - - - - - -- - - -


\blue\textsf{\textbf{\underline{\underline{Question:-}}}}

Evaluate the expression a²-18+4b when a=3 and b=-6


\blue\textsf{\textbf{\underline{\underline{Answer and How to Solve:-}}}}

Substitute 3 in lieu of a and -6 in lieu of b:-

(3)²-18+4(-6)

9-18+4(-6)

On further simplification,

9-18-24


\dashrightarrow\bigstar\boxed{\boxed{\underline{\bold{-33}}}}\dashleftarrow

Good luck.

-- - - - - - - - - - - - - - - - - - -- - - ---- - - -- - - - - - - - - - - - - - - - - - - - -- - -

User Harunurhan
by
4.7k points
5 votes

Answer:

D

Explanation:


{3}^(2) - 18 + 4( - 6) \\ 9 - 18 + ( - 24) \\ - 9 + ( - 24) \\ = - 33

User Howiecamp
by
5.5k points